2013
DOI: 10.1016/s0034-7094(13)70228-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simple Clinical Predictors on Preoperative Diagnosis of Difficult Endotracheal Intubation in Obese Patients

Abstract: The clinical and polysomnographic diagnosis of OSA proved useful in the preoperative diagnosis of difficult laryngoscopy. Obese patients are more prone to difficult facemask ventilation and laryngoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
3
9
1
1
Order By: Relevance
“…compared with those of our study and others. 8,11,14,16 Moreover, our results suggested that neither BMI nor modified Mallampati score were correlated with difficult laryngoscopy, contrasting with some previous studies 6–8 but agreeing with others. 9–12 Eiamcharoenwit et al reported that neck circumference and modified Mallampati score show limited predictive performance for difficult intubation among obese parturients.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…compared with those of our study and others. 8,11,14,16 Moreover, our results suggested that neither BMI nor modified Mallampati score were correlated with difficult laryngoscopy, contrasting with some previous studies 6–8 but agreeing with others. 9–12 Eiamcharoenwit et al reported that neck circumference and modified Mallampati score show limited predictive performance for difficult intubation among obese parturients.…”
Section: Discussioncontrasting
confidence: 68%
“…6–16 Differences in the measurements and definitions of difficult airway and the evaluated airway characteristics are potentially responsible for the discrepancies in previous findings. We found that greater neck circumference was linked to difficult laryngoscopy, in line with some previous studies 8,11,14 but not the study by Magalhaes et al 16 This might be explained by the significantly lower BMI and neck circumference in the study by Magalhaes et al . compared with those of our study and others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations